2012
DOI: 10.1007/s10875-012-9854-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Genetic Profiles of 44 Patients with Severe Combined Immunodeficiency (SCID): Report from Shanghai, China (2004–2011)

Abstract: Severe combined immunodeficiency (SCID), a rare type of genetic associated immune disorder, is poorly characterized in mainland China. We retrospectively reviewed 44 patients with SCID who received treatment from 2004 to 2011 in Shanghai, China, and herein summarize their clinical manifestations and immunological and preliminary genetic features. The male-to-female ratio was 10:1. Twenty five patients presented with X-SCID symptoms. Only one patient was diagnosed before the onset of symptoms due to positive fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
6
21
1
3
Order By: Relevance
“…SCID patients have an approximately 400‐fold increase in risk of having localized BCG complication and 33 000‐fold increase in risk of having disseminated complications compared to the general population . However, another study in Shanghai revealed a different result; 58% of the patients with SCID who were inoculated with BCG had BCG‐related manifestations, of which 15% were disseminated BCG vaccine complications, and 85% were local complications . In disseminated BCG infection, involvement of extra‐regional lymph nodes, skin, and lungs is common, whereas involvement of liver, spleen, and bones is unusual .…”
Section: Discussionmentioning
confidence: 99%
“…SCID patients have an approximately 400‐fold increase in risk of having localized BCG complication and 33 000‐fold increase in risk of having disseminated complications compared to the general population . However, another study in Shanghai revealed a different result; 58% of the patients with SCID who were inoculated with BCG had BCG‐related manifestations, of which 15% were disseminated BCG vaccine complications, and 85% were local complications . In disseminated BCG infection, involvement of extra‐regional lymph nodes, skin, and lungs is common, whereas involvement of liver, spleen, and bones is unusual .…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of 1 in 2,500 vaccinees presenting with localized BCG complications and 1 in 100,000 developing disseminated complications represent a fair estimate of the prevalence of such complications 1 9 . When focused exclusively on patients diagnosed with SCID, the prevalence of BCG complications has been estimated to be higher than in the general population 10-12 , although definitive impact has not previously been established.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant phenotype of SCID varies according to the country. For example, in China, 25 of 44 SCID patients had X-linked SCID [12], and in Serbia and Montenegro, 12 of 21 patients with SCID and Omenn syndrome belonged to the T -B -NK + SCID phenotype; 11 had mutations in RAG1 or RAG2 and 1 had mutations in the Artemis gene [3]. In Greece, 12 of 30 SCID patients (40%) were T -B -NK + [13].…”
Section: Discussionmentioning
confidence: 99%